Sistemas eletrônicos de iluminação baseados nos conversores CA/CA - Tomm, Fabio Luis (2011)
This thesis proposes to improve the efficiency of public illumination systems by means of AC chopper based power converters. A comparative study of high performance AC/AC converters feeding high pressure sodium lamps on mains frequency is presented. These converters are obtained using standard DC/DC topologies with bi-directional switches (four quadrants). A high pressure lamp ballast design methodology is also presented, based on the suppositions of high input power factor and without exciting acoustic resonances at destructive levels. The topologies used are the Buck-Boost, Ćuk, SEPIC and ZETA operating on continuous current mode, with or without input filter, and an ignition circuit. The converters' switching frequencies are 33 kHz feeding the lamp at low frequency (mains frequency). The ignition circuit providing the high voltage required to guarantee the initial arc to start-up the lamp, is presented, analyzed and optimized in the thesis. To control the ballast a 32 bits microcontroller is used, contributing to reduce the component count and the overall system cost. The base to propose a new control design methodology and power circuit parts specification is the Brazilian standards and a comparison with the electromagnetic ballasts output waveforms. Experimental results supplying a 70 W HPS lamp, connected to the mains (220 V ±20% e 60 Hz) through the proposed ballasts, are presented in order to validate the thesis.